Residence time and survival studies for Enterococcus faecium as a surrogate for Salmonella during preconditioning and extrusion processing of dry expanded pet food - Zhou, Tiya (Kansas State University, 2016)
Validation studies on process equipment are an important step for effective pathogenic control during dry expanded pet food manufacturing. The preconditioner is used to hydrate, mix and pre-cook raw materials before extrusion of pet food. The High-Intensity-Preconditioner (HIP) was designed with two independently driven shafts, thus offering control of both shaft speed and rotational direction with potential for improving residence time and thus pathogen inactivation. Residence time distribution (RTD) of raw dog food mix was impacted by the HIP process parameters (average residence time varying between 104-178 s for dry experiment and 65-177 s with steam addition) depending on shaft speed and direction. In general, increase in shaft speed resulted in shorter residence time with the larger shaft having a greater impact than the smaller shaft. Rotational direction of shafts also had an effect on average residence time (a maximum difference of 37 s was noticed between treatments with different shaft directions and the same speed). The uniformity of residence time distribution (difference of 97-132 s between 15 and 85 percentiles of the cumulative RTD) also varied considerably with process conditions, with uniformity increasing with shaft speed.  Enterococcus faecium (ATCC® 8459™) was chosen as a surrogate for Salmonella for microbial inactivation studies on the HIP. Both HIP shaft speed (200 and 300 rpm) and process temperature (67-70°C and 89-91°C) impacted E.faecium survival. Lower shaft speed (corresponding to longer residence time) or higher temperature led to greater E.faecium inactivation. A 5 log CFU/g of E.faecium was reduced using selective agar (m-Enterococcus or mE agar) after treatment with high temperature, but approximately 3.5 log CFU/g of E.faecium reduced on non-selective agar (Brain Heart Infusion or BHI agar). Uneven heat distribution, inadequate residence time and system instability might have negatively affected the inactivation. Microbial inactivation, with E.faecium as surrogate, was also studied for the complete dry expanded pet food process using a pilot-scale single-screw extruder with a regular double shaft preconditioner. Meal was inoculated with E.faecium at 6 log CFU/g and processed. Preconditioner downspout temperature ranged from 89-94°C and extrusion die temperature was between 120-140°C. Complete inactivation was observed after extrusion.
Keywords: Pet food; Extrusion; Preconditioning; Salmonella; Enterococcus faecium; Food safety